Impact of a moderate-intensity aerobic exercise intervention on systemic and uterine natural killer cells in women with unexplained recurrent pregnancy loss - Gurbanova, Aysel; Lombardi, Amber E. M.; Habets, Denise H. J.; Al-Nasiry, Salwan; Spaanderman, Marc E. A.; de Jonge, Marien I.; Meuleman, Tess; Wieten, Lotte; van der Molen, Renate G. (Frontiers in Immunology, 2025)
IntroductionRecurrent pregnancy loss (RPL) is associated with altered immune phenotypes and functions. It has been proposed that physical exercise might impact the immune system. Therefore, we evaluated the effect of a personalized 3-month moderate-intensity aerobic exercise intervention on the immune system of women with unexplained RPL (uRPL). Given the suggested supportive role of Natural Killer (NK) cells during early pregnancy, we focused on numerical, phenotypic, and functional changes in peripheral NK (pNK) and uterine NK (uNK) cells.MethodsMononuclear cells were isolated from peripheral blood (PB) (n=23) and menstrual blood (MB) (n=22) of women with uRPL. NK cell phenotypes were assessed with comprehensive flow cytometry panels. NK cell function was assessed with degranulation assays and intracellular staining of interferon-γ (IFN-γ), perforin and granzyme-B in a subgroup of women due to lower availability of samples (n=12).ResultsAttendance to the exercise intervention was overall 95%, which resulted in effects on the phenotype and function of pNK cells. We found a significant reduction in the median fluorescent intensity of CD161 (464 vs 410, p=0.011), NKp30 (432 vs 376, p=0.018), and NKG2A (886 vs 732, p=0.039) in pNK cells after exercise, while no differences were observed in uNK cells. We also observed decreased percentages of IFN-γ+ pNK cells (49% vs 25.2%, p=0.027) after exercise.DiscussionOur study shows promising results, suggesting that exercise can impact pNK cell phenotype and function in women with uRPL. Following the changes in pNK phenotype and function suggest a lower pro-inflammatory state post-exercise. Whether these exercise-induced phenotypic and functional changes of pNK cells impact subsequent pregnancies remains to be studied. The study details are available through HYPERLINK “https://clinicaltrials.gov/”Home | ClinicalTrials.gov, trial ID: HMOVE